2006
DOI: 10.1088/1742-6596/46/1/037
|View full text |Cite
|
Sign up to set email alerts
|

Simulating solidification in metals at high pressure: The drive to petascale computing

Abstract: We investigate solidification in metal systems ranging in size from 64,000 to 524,288,000 atoms on the IBM BlueGene/L computer at LLNL. Using the newly developed ddcMD code, we achieve performance rates as high as 103 TFlops, with a performance of 101.7 TFlop sustained over a 7 hour run on 131,072 cpus. We demonstrate superb strong and weak scaling. Our calculations are significant as they represent the first atomic-scale model of metal solidification to proceed, without finite size effects, from spontaneous n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…As in other recent Ta4 MGPT applications [2,4,6,21,28,31,36,37], all of the melt methods discussed below apply the Ta6.8x potentials using the advanced matrix representation of MGPT [6], as implemented in the parallel molecular dynamics code ddcMD [39]. In ddcMD, the angular functions L, P, and M in Eqs.…”
Section: B Methods Of Melt Calculationmentioning
confidence: 99%
“…As in other recent Ta4 MGPT applications [2,4,6,21,28,31,36,37], all of the melt methods discussed below apply the Ta6.8x potentials using the advanced matrix representation of MGPT [6], as implemented in the parallel molecular dynamics code ddcMD [39]. In ddcMD, the angular functions L, P, and M in Eqs.…”
Section: B Methods Of Melt Calculationmentioning
confidence: 99%
“…It has been shown that, under specific circumstances, adding computing units might hamper applications completion time, as a larger node count implies a higher probability of reliability issues. This directly translates into a lower efficiency of the machine, which equates to a lower scientific throughput [Streitz et al 2006]. It is estimated that the MTTF of High Performance Computing (HPC) systems might drop to about one hour in the near future [Cappello 2009].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, under specific circumstances, adding computing units might increases applications completion time, as a larger node count implies a higher probability of reliability issues. This directly translates into a lower efficiency of the machine, which equates to a lower scientific throughput [24]. It is estimated that the MTTF of High Performance Computing (HPC) systems might drop to about one hour in the near future [7].…”
Section: Introductionmentioning
confidence: 99%